Formula Merawat Damai Dan Kerukunan Untuk Pembangunan Indonesia Yang Berkelanjutan - Rizqi Wahyudi; Bastiar Bastiar; ismail Ismail (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2020)
This article aims to understand the contribution of the Acehnese Academics, scholars and borders in formulating ways to care for peace and religious harmony in Aceh for the sustainable development of Indonesia. Fatally the harmony of life between religious communities in Indonesia in particular still faces many obstacles in its achievement such as the problem of houses of worship, deception, defamation of religion and problems of relations between religious people. Method used is descriptive qualitative with a phenomenological approach. How to monitor and maintain peace in a majestic Indonesia is First by applying the principle of Islamic communication among various communities. Both optimize the function of unifying institutions, such as unifying different vision and mission of community members in one group with the same vision and mission but "not equating aqeedah vision." Thirdly tolerance education with a content of tolerance in Islam, management of conflict, cultivators of mutual love and mutual affection, respect for respect, which is done both by the government formally through educational and non-formal curricula through discussions and studies organized by border preachers, scholars, and academics.